Trigonachras postardanjeisin - Hoo, P.K.; Colin Ruzelion Maycock; Damit, A.; Khoo, E.; Nilus, R.; Sugau, J.; Tsen, S.; Pereira, J.T. (International Union for Conservation of Nature and Natural Resources, 2020)
Trigonachras postardanjeisin is restricted to two sites in Tawai Forest Reserve. The estimated area of occupancy (AOO) and extent of occurrence (EOO) are both 8 km2 and are not in decline. The area is a Totally Protected Area (TPA) where the habitats are being preserved. The possible threat is forest fire which could drive the species towards Critically Endangered or Extinct in the near future, in a single event. Hence, it is assessed as Vulnerable. Trigonachras postardanjeisin is endemic to Sabah, Malaysia. It is recorded from two localities within Tawai Forest Reserve.